Exogenous jasmonic acid and salicylic acid enhance selenium uptake and mitigate cadmium accumulation in pak choi (Brassica chinensis L.) grown in selenium-rich, high-cadmium soil - Chen, Jin-Ping; Qin, Jie; Xing, Ying; Liao, Qing; Pan, Li-Ping; Zeng, Cheng-Cheng; Liu, Yong-Xian (Frontiers in Plant Science, 2025)
Plant hormones are known to regulate the uptake and distribution of mineral elements, including heavy metals, in crops. This study evaluated the effects of exogenous jasmonic acid (JA) and salicylic acid (SA), applied individually or in combination, on selenium (Se) enrichment and cadmium (Cd) mitigation in pak choi (Brassica chinensis L.) cultivated in Se-rich and high-Cd soils. Hormone treatments significantly increased shoot Se content by 33.7%-62.3% compared to the control, with the highest level Se accumulation observed under combined application of 50 μmol·L-1 JA and 50 μmol·L-1 SA. Cd accumulation in shoots decreased by 11.7%-29.3% in JA-containing treatments, with the same combined producing the lowest shoot Cd levels. JA alone increased root Cd content, while SA treatments reduced it. Individual hormone treatments elevated root levels of phytochelatins (PCs), glutathione (GSH), and metallo-thioneins (MTs), while the combined treatment future increased PCs and GSH, but decreased MTs and non-protein thiols (NPTs). Antioxidant enzyme activities (SOD, CAT, POD), chlorophyll content and shoot fresh weight also increased in JA-containing treatments. Taken together, foliar application of JA combined SA offers a promising strategy to enhance Se biofortification, reduce Cd accumulation, and promote biomass production in pak choi grown in Se-rich and high-Cd soils.